Molecular signatures in Mendelian neurodevelopment: a focus on ubiquitination driven DNA methylation aberrations - van der Laan, Liselot; ten Voorde, Nicky; Mannens, Marcel M. A. M.; Henneman, Peter (Frontiers in molecular neuroscience, 2024)
Mendelian disorders, arising from pathogenic variations within single genetic loci, often manifest as neurodevelopmental disorders (NDDs), affecting a significant portion of the pediatric population worldwide. These disorders are marked by atypical brain development, intellectual disabilities, and various associated phenotypic traits. Genetic testing aids in clinical diagnoses, but inconclusive results can prolong confirmation processes. Recent focus on epigenetic dysregulation has led to the discovery of DNA methylation signatures, or episignatures, associated with NDDs, accelerating diagnostic precision. Notably, TRIP12 and USP7, genes involved in the ubiquitination pathway, exhibit specific episignatures. Understanding the roles of these genes within the ubiquitination pathway sheds light on their potential influence on episignature formation. While TRIP12 acts as an E3 ligase, USP7 functions as a deubiquitinase, presenting contrasting roles within ubiquitination. Comparison of phenotypic traits in patients with pathogenic variations in these genes reveals both distinctions and commonalities, offering insights into underlying pathophysiological mechanisms. This review contextualizes the roles of TRIP12 and USP7 within the ubiquitination pathway, their influence on episignature formation, and the potential implications for NDD pathogenesis. Understanding these intricate relationships may unveil novel therapeutic targets and diagnostic strategies for NDDs.